Development Of Stoichiometry Learning Materials Based On PBL Integrated With SDGs Used By Nearpod To Improve Learning Outcomes and Environmental Literacy - Unsa, Nurul; Haryani, Sri; Widiarti, Nuni (Universitas Negeri Semarang, 2025)
This research aims to develop chemistry teaching materials on stoichiometry material based on Problem Based Learning (PBL), integrated with Sustainable Development Goals (SDGs) issues, and supported by Nearpod digital technology. The background of this research is the low learning outcomes of students caused by inadequate teaching materials which influence the lack of active involvement of students in the learning process, as well as the need to improve students' environmental literacy. The research uses the 4-D development model (Define, Design, Develop, Disseminate). The research subjects consisted of class X students of MAN 1 Jepara who were divided into a control class and an experimental class. Data were collected through observation, interviews, expert validation, implementation tests, effectiveness tests, and student and teacher response questionnaires. The validation results by material experts show that the teaching materials are declared very feasible with a validity value of the Aiken's V index of 0.898 (high category), reliability of material experts (Percentage of Agreement): 98.87% (reliable), and percentage of feasibility of material experts: 92.36% (very feasible). The validation results by media experts showed that the teaching materials were declared very feasible with a validity value of the Aiken's V index of 0.939 (high category), reliability of media experts (Percentage of Agreement): 97.6% (reliable), percentage of feasibility of media experts: 95.45% (very feasible). The effectiveness test showed an increase in the learning outcomes of the experimental class (N-Gain = 0.45) and the environmental literacy of the experimental class (N-Gain = 0.34) in the moderate category and higher than the control class. The results of the Pearson correlation test showed a significant positive relationship between learning outcomes and environmental literacy (r = 0.405, p < 0.01). Thus, this teaching material is effective in improving students' learning outcomes and environmental literacy.